DOI: 10.31274/rtd-180813-16804
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomic analysis of Turnip mosaic virus infection in Arabidopsis thaliana

Abstract: All rights reserved. by ProQuest Information and Learning Company. TABLE OF CONTENTS CHAPTER 1. GENERAL INTRODUCTION 1.1. Significance and objectives 1.2. Literature review-the compatible interaction between potyviruses and plant host 1.3. Dissertation organization 15 1.4. References 16 CHAPTER 2. SPATIAL ANALYSIS OF ARABIDOPIS THALIANA GENE EXPRESSION IN RESPONSE TO TURNIP MOSAIC VIRUS INFECTION 2.1. Abstract 2.2. Introduction 23 2.3. Results 2.4. Discussion 34 2.5. Material and Methods 2.6. Acknowledgements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 109 publications
1
0
0
Order By: Relevance
“…A '40S ribosomal protein S20' also interacted with the CP of ToLCV, which is involved in subcellular localization, protein activity regulation, protein with binding function or cofactor requirement and transcription (Zhou et al 2015;Lost and Jain 2019). Similar interaction was reported in Arabidopsis thaliana with Turnip mosaic virus infection (Yang 2007). Some disease manipulative proteins such as 'zinc finger X-linked protein ZXDA-like', a DNA binding protein, which are able to target specifically and manipulate disease-causing genes (Cassandri et al 2017) was also found.…”
Section: Discussionsupporting
confidence: 61%
“…A '40S ribosomal protein S20' also interacted with the CP of ToLCV, which is involved in subcellular localization, protein activity regulation, protein with binding function or cofactor requirement and transcription (Zhou et al 2015;Lost and Jain 2019). Similar interaction was reported in Arabidopsis thaliana with Turnip mosaic virus infection (Yang 2007). Some disease manipulative proteins such as 'zinc finger X-linked protein ZXDA-like', a DNA binding protein, which are able to target specifically and manipulate disease-causing genes (Cassandri et al 2017) was also found.…”
Section: Discussionsupporting
confidence: 61%